Higher Education Policy Model During The Pandemic: Lesson Learned From University Students - Eko Budi Sulistio; Simon Sumanjoyo Hutagalung (Goodwood Publishing, 2022)
Purpose: The primary purpose of this study is to identify models that contribute to the effectiveness of policies and institutions in managing online learning in Colleges during the mass pandemic. Methodology: This research will be conducted using a mixed method. The survey was carried out using a questionnaire to groups of college students. The data analysis includes statistical analysis to determine the frequency and description of the survey data obtained. Results: Several aspects must be intervened from this condition. This is related to managing incentives and financial assistance to student groups. There is a need for planning and adjustments regarding financial aid management. Then, the aspect of stakeholder involvement will be related to the role of educational institutions as regional, central and non-government actors. The aspect of policy adjustment will intersect with legislative institutions or policies at the regional and central levels. Limitations: This research is limited to regional scope studies, so it requires comparison with other regions with more adequate educational resources. Contribution: In the future, the model can be developed to strengthen the need for a mixed education model by combining technology and a human touch so that the online education model can feel more humanist. Novelty: The resulting model combines policy and institutional aspects as an intervention package for higher education in times of crisis, such as a pandemic.